2013
DOI: 10.3923/pjbs.2013.1597.1600
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Supplementary Vitamins C and E on Anxiety, Depression and Stress in Type 2 Diabetic Patients: A Randomized, Single-blind, Placebo-controlled Trial

Abstract: Diabetes mellitus as one of the most prevalent endocrine disease is associated with high oxidative stress. Anxiety, stress and depression are common neuropsychiatric features in diabetic patients. Hyperglycemia leads to increased oxidative stress which in turn diminishes antioxidant defense system. On the other hand oxidative stress is the leading cause of depression and anxiety disorders. Thus, it seems that diabetes could accelerate the trend of psychiatric diseases. In this randomized single-blind study, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 10 publications
2
41
0
6
Order By: Relevance
“…Gautam et al [ 171 ] observed that patients with generalized anxiety disorder had significantly lower Vit C levels in comparison with healthy controls, whereas 6-week vitamins supplementation (vitamin C accompanied with A and E) led to a significant reduction in anxiety scores [ 171 ]. Mazloom et al [ 190 ], in turn, showed that short-term supplementation of Vit C (1000 mg/day) reduced anxiety levels (evaluated basing on Depression Anxiety Stress Scales 21-item) in diabetic patients. This effect was exerted through alleviating oxidative damage.…”
Section: Role Of Vitamin C In Psychiatric Disordersmentioning
confidence: 99%
“…Gautam et al [ 171 ] observed that patients with generalized anxiety disorder had significantly lower Vit C levels in comparison with healthy controls, whereas 6-week vitamins supplementation (vitamin C accompanied with A and E) led to a significant reduction in anxiety scores [ 171 ]. Mazloom et al [ 190 ], in turn, showed that short-term supplementation of Vit C (1000 mg/day) reduced anxiety levels (evaluated basing on Depression Anxiety Stress Scales 21-item) in diabetic patients. This effect was exerted through alleviating oxidative damage.…”
Section: Role Of Vitamin C In Psychiatric Disordersmentioning
confidence: 99%
“…Diabetes has also been associated to periodontal disease and vitamin C supplementation together with dental maneuvers has been shown to improve chronic periodontitis in newly diagnosed type 2 diabetic subjects [ 78 ]. Vitamin C has also been shown to reduce anxiety levels but not stress and depression scores in diabetes [ 79 ]. Three month supplementation of vitamins C and E decreased hypertension, blood glucose while increasing superoxide dismutase and glutathione levels [ 80 ].…”
Section: Vitamins and Diabetesmentioning
confidence: 99%
“…There are some promising reports about the beneficial effect of vitamin C in animal models of depression. ‘Nevertheless, supplementary vitamins C did not decrease depression in type 2 diabetic patients in a randomized, single-blind, placebo-controlled trial’ [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 21-item Beck Depression Rating Scale score decreased from 14.133 ± 4.37 to 3.233 ± 7.08 ( P < 0.018) [ 15 ]. Nevertheless, supplementary vitamin C (1,000 mg/day) did not decrease the depression score in type 2 diabetic patients in a randomized, single-blind, placebo-controlled trial [ 9 ].…”
Section: Introductionmentioning
confidence: 99%